Proceedings of the Tenth Workshop on Visualization for Cyber Security 2013
DOI: 10.1145/2517957.2517962
|View full text |Cite
|
Sign up to set email alerts
|

Flexible web visualization for alert-based network security analytics

Abstract: This paper describes a web-based visualization system designed for network security analysts at the U.S. Army Research Laboratory (ARL). Our goal is to provide visual support to the analysts as they investigate security alerts for malicious activity within their systems. Our ARL collaborators identified a number of important requirements for any candidate visualization system. These relate to the analyst's mental models and working environment, and to the visualization tool's configurability, accessibility, sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
(14 reference statements)
0
14
0
Order By: Relevance
“…Additionally, several histograms are provided with dual purposes: to give an overview of the data and to guide users in their analysis. Hao et al [146] also describe a web-based visualization system designed for network security analysts at the U.S. Army Research Laboratory (ARL). This tool aims at visual support to the analysts to give better insights about security alerts for malicious activity within their systems.…”
Section: B State Of the Artmentioning
confidence: 99%
“…Additionally, several histograms are provided with dual purposes: to give an overview of the data and to guide users in their analysis. Hao et al [146] also describe a web-based visualization system designed for network security analysts at the U.S. Army Research Laboratory (ARL). This tool aims at visual support to the analysts to give better insights about security alerts for malicious activity within their systems.…”
Section: B State Of the Artmentioning
confidence: 99%
“…Many authors of the VizSec papers are not consistent in their use of these terms. Most usage scenarios are reported in a section called "case study," and others have reported their formal case studies under other names, such as an "example analysis session" [17]. Usage scenarios can serve a purpose, but it is important to note that a lack of connection back to real users or real data (or both) may question the validity and utility of the evaluated tool.…”
Section: Evaluation Using Case Studiesmentioning
confidence: 99%
“…The cluster tree visualization allows analysts to interactively choose subsets of members to compare, analyze and visualize, allowing them to efficiently discover traffic with similar or unique patterns. It also meets the design requirements demonstrated in our prototype security visualization system, built in the collaboration with security analysts at the U.S. Army Research Laboratory (ARL) [8]:…”
Section: Introductionmentioning
confidence: 69%